2018
DOI: 10.1056/nejmoa1700209
|View full text |Cite
|
Sign up to set email alerts
|

Household-Contact Investigation for Detection of Tuberculosis in Vietnam

Abstract: Household-contact investigation plus standard passive case finding was more effective than standard passive case finding alone for the detection of tuberculosis in a high-prevalence setting at 2 years. (Funded by the Australian National Health and Medical Research Council; ACT2 Australian New Zealand Clinical Trials Registry number, ACTRN12610000600044 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
158
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 19 publications
14
158
1
2
Order By: Relevance
“…In an early study of INH treatment in patients with fibrotic lung lesions, placebo recipients had a 1.4% cumulative 5‐year TB risk that was decreased by 75% among those receiving 12 months of INH . A study in Vietnam found that active surveillance in household contacts was better than passive surveillance alone for diagnosing future active TB . Successful LTBI treatment strategies have been demonstrated in Thailand among PLWH and in Republic of Korea among people receiving a TNF‐alpha blocker .…”
Section: The Challenge Of Implementing National Tb Elimination Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early study of INH treatment in patients with fibrotic lung lesions, placebo recipients had a 1.4% cumulative 5‐year TB risk that was decreased by 75% among those receiving 12 months of INH . A study in Vietnam found that active surveillance in household contacts was better than passive surveillance alone for diagnosing future active TB . Successful LTBI treatment strategies have been demonstrated in Thailand among PLWH and in Republic of Korea among people receiving a TNF‐alpha blocker .…”
Section: The Challenge Of Implementing National Tb Elimination Plansmentioning
confidence: 99%
“…57 A study in Vietnam found that active surveillance in household contacts was better than passive surveillance alone for diagnosing future active TB. 73 Successful LTBI treatment strategies have been demonstrated in Thailand among PLWH and in Republic of Korea among people receiving a TNF-alpha blocker. [73][74][75][76] These examples demonstrate that opportunities exist in carefully selected settings to combine robust strategies for diagnosing active TB with LTBI treatment to accelerate declines in TB disease.…”
Section: The Challenge Of Implementing National Tb Elimination Plansmentioning
confidence: 99%
“…In terms of addressing TB control at a broader, community‐wide level, there have been calls to expand active case‐finding programmes, which aim to decrease the TB burden by identifying undiagnosed cases . However, despite historical success of population‐based interventions including isoniazid preventive therapy and active case‐finding, recent trials have yielded mixed results in high‐burden settings (Table ) . These data suggest that more targeted case‐finding programmes or location‐based environmental or administrative controls might be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from Churchyard et al ., with the addition of data from Okada et al . and Fox et al ., with permission…”
Section: Introductionmentioning
confidence: 99%
“…Approaches towards mitigating these factors could involve active case-finding (ACF) 34 . India's 7 recent National Strategic Plan underlines the potential importance of ACF in risk groups such as 8 urban slums 16 , while recent work in Viet Nam has also demonstrated the potential value of 9 screening close contacts of diagnosed TB cases, together with longitudinal followup of these 10 contacts 35 . However, it is also possible for the patient delay to be impacted by measures to 11 improve the demand for TB services; for example, social protection mechanisms 36 could have 12 the secondary effects of encouraging TB symptomatics to come forward for care 37 .…”
mentioning
confidence: 99%